2022
DOI: 10.1073/pnas.2210299119
|View full text |Cite
|
Sign up to set email alerts
|

Control of resistance against bacteriophage killing by a metabolic regulator in meningitis-associated Escherichia coli

Abstract: Ecologically beneficial traits in bacteria are encoded by intrinsic and horizontally acquired genes. However, such traits are not universal, and the highly mosaic nature of bacterial genomes requires control at the transcriptional level to drive these processes. It has emerged that regulatory flexibility is widespread in the Escherichia coli species, whereby preexisting transcription factors can acquire new and unrelated roles in regulating beneficial traits. DsdC is the regulator of D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…DsdC is a well-studied D-Serine responsive transcriptional regulator that is required for catabolism of D-Serine via activation of dsdXA [16]. Our recent work has shown that DsdC does not only regulate the dsdCXA operon and is in fact capable of binding of numerous areas of the genome [53]. We hypothesized that the repression of the pks locus by D-Serine might be mediated by DsdC.…”
Section: The D-serine Metabolism Locus Is Not Essential For Repressio...mentioning
confidence: 99%
“…DsdC is a well-studied D-Serine responsive transcriptional regulator that is required for catabolism of D-Serine via activation of dsdXA [16]. Our recent work has shown that DsdC does not only regulate the dsdCXA operon and is in fact capable of binding of numerous areas of the genome [53]. We hypothesized that the repression of the pks locus by D-Serine might be mediated by DsdC.…”
Section: The D-serine Metabolism Locus Is Not Essential For Repressio...mentioning
confidence: 99%